2013
DOI: 10.1007/s12663-013-0532-5
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Clinical Study of Marginal Bone Level Changes with Two Different Screw-Implant Types: Comparison Between Tissue Level (TE) and Bone Level (BL) Implant

Abstract: Aim The objective of this retrospective cohort study was to compare the amount of marginal bone loss (MBL) in a bonelevel and a soft-tissue-level implant system, both of which have similar intra-bony shape and surface composition. A subgroup analysis was done to compare the amount of MBL of each implant type in relation to the different vertical placement within the respective groups of implants. Materials and Methods Records of all patients who underwent implantation for replacement of teeth using comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…No significant differences in bone loss were detected. Contradictorily, the clinical retrospective cohort study that aimed to compare the amount of marginal bone loss in bone- level and soft-tissue-level implant systems found no statistically significant difference between the two groups at time periods of 6 - 12 months, but in later time periods there was a slightly greater amount of marginal bone loss around tissue-level implants compared to bone-level implants [48]. …”
Section: Discussionmentioning
confidence: 99%
“…No significant differences in bone loss were detected. Contradictorily, the clinical retrospective cohort study that aimed to compare the amount of marginal bone loss in bone- level and soft-tissue-level implant systems found no statistically significant difference between the two groups at time periods of 6 - 12 months, but in later time periods there was a slightly greater amount of marginal bone loss around tissue-level implants compared to bone-level implants [48]. …”
Section: Discussionmentioning
confidence: 99%
“…However, if the radiograph is of high quality, Persson and colleagues and Akesson described the orthopantomogram as examination of choice for the evaluation of the marginal bone level around teeth. In the literature, peri‐implant bone resorption for the same tapered implant system ranged between 0.4 mm and 0.93 mm with a follow‐up between 16 and 60 months (Table ), indicating promising results concerning marginal bone stability . In a recent review, Abrahamsson and colleagues indicated that controlled prospective studies examining the effect of implant surface and designs on peri‐implant bone resorption with a follow‐up of ≥3 years are rare.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, peri-implant bone resorption for the same tapered implant system ranged between 0.4 mm and 0.93 mm with a follow-up between 16 and 60 months ( Table 2), indicating promising results concerning marginal bone stability. 28,32,46 In a recent review, Abrahamsson and colleagues 47 indicated that controlled prospective studies examining the effect of implant surface and designs on peri-implant bone resorption with a follow-up of 33 years are rare. One study showed significantly improved marginal bone preservation for implants with a conical and micro-threaded marginal collar compared with implants with a cylindrical and nonthreaded marginal portion after 3 years in function.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, since the dentures are removable, this greatly helps in oral hygiene maintenance and prevents malodor. The use of tissue level implants provides easier access to the abutment platform, which improves operator comfort as well as patient maintenance in such cases [23].…”
Section: Discussionmentioning
confidence: 99%